Agile Processes in Software Engineering and Extreme Programming - Workshops XP 2022 Workshops, Copenhagen, Denmark, June 13-17, 2022, and XP 2023 Workshops, Amsterdam, The Netherlands, June 13-16, 2023, Revised Selected Papers - Kruchten, Philippe; Gregory, Peggy (Lecture Notes in Business Information Processing, 2024)
This open access book constitutes papers from the research workshops presented at XP 2022 and XP 2023, respectively the 23rd and 24th International Conferences on Agile Software Development, held on June 13-17, 2022 at the IT University of Copenhagen, Denmark and June 13-16, 2023 in Amsterdam, Netherlands. XP is the premier agile software development conference combining research and practice. It is a unique forum where agile researchers, practitioners, thought leaders, coaches, and trainers get together to present and discuss their most recent innovations, research results, experiences, concerns, challenges, and trends. XP conferences provide an informal environment to learn and trigger discussions and welcome both people new to agile and seasoned agile practitioners. In 2022, the following workshops took place: ● 3rd International Workshop on Agility with Microservices Programming ● 2nd International Workshop on Agile Sustainability ● Agile and Education In 2023, six workshops were held: ● Workshop on Organisational Debt and Large-Scale Agile ● Workshop on Software-Intensive Business ● Workshop on Global and Hybrid Work ● Workshop on Fear-Based Agile Transformation ● Workshop on AI-assisted Agile ● Workshop on Agile-Quantum Software Engineering In 2022, 6 workshop papers were accepted for publication in these post-proceedings, out of 11 submissions, and in 2023, 15 papers were accepted for publication out of 38 submissions.